P-078 LAPAROSCOPIC TREATMENT OF UMBILICAL HERNIA IN A COMMUNITY HOSPITAL SETTING. (13th October 2022) - Agresta, F; Mazzarolo, G; Licitra, E; Pontarolo, N; Savino, G; Montori, G
Abstract: Introduction: Umbilical Hernia is a common ventral hernia in the adult population. The classical approach was represented by open repair, but in recent years laparoscopic treatment is increasingly adopted and it can present some intraoperative and post-operative advantages. Materials and methods: We prospectively analyzed a case series of 50 laparoscopic primary and incisional umbilical hernia repairs performed between January 1 st, 2020, and December 31 st, 2021. We collected data concerning age, sex, hernia defect size, operative time, and complications according to Clavien-DindoClassification, recurrence at 6 months, and 1-year follow-up. Results: We performed laparoscopic umbilical hernia repairs in 50 patients (32males, 18females);mean age52.1year-old(range30–82y.o.).Mean defect size was4.5cm(3–6.8cm).All procedures were performed under general anesthesia and with 5mm trocars and optic and under pneumoperitoneum pressure set until 10 mmHg as the maximum value. In all cases we applied a transparent, lightweight, ultra-thin, nonabsorbable surgical prosthesis in polypropylene, made by a monofilament macroporous mesh and a transparent film. and we performed closure of fascia with adsorbable stitches. Mean Operative time:40minutes(30–65min.).No complications and recurrences were reported. Conclusions: Laparoscopic treatment of umbilical hernia is a safe and feasible procedure; indeed, we consider reducing hernia from the abdominal cavity generally better than the open approach and composite mesh positioning with direct fascial closure usually allows a satisfying repair of the defect.